(untitled) (Health Renaissance, 2017)
Background: Wild honey has been traditionally been used by indigenous people for its medicinal, aphrodisiac and hallucinogenic properties in Nepal and some other countries. Wild (mad) honey intoxication is one of the rarest presentations to emergency department and is caused by ingestion of wild honey obtained from the nectar of Rhododendron species on the higher altitudes. The cause of mad honey poisoning is the toxin grayanotoxin, found in such wild honey. It can also be caused by consuming the leaves, flowers of Rhododendron from Himalayan belt. Wild honey intoxication has widely been reported from Turkey and the regions around the Black Sea. Some cases have been reported in the few hospitals in Kathmandu and Chitwan. However, such cases have rarely been reported in eastern Nepal. The intoxication might present with mild symptoms of gastrointestinal, cardiovascular and neurological systems or might also present in rare life threatening form with AV block and cardiovascular collapse. Here, we report a case of a seventy three years old man who presented to our emergency department with cardiovascular collapse in the form of severe bradycardia, AV block and hypotension after wild honey consumption. Health Renaissance 2015;13(2): 170-172